Organizational Climate dan Workplace Incivility Behavior pada Perawat - Fitrimahsha, Arina; Lukman, Lukman; Rahmat, Abdul (Jurnal Psikologi TALENTA, 2024)
Workplace Inciviliy Behavior is incivility behavior in the workplace and deviates from applicable work norms both in writing and unwritten. One of the factors that can affect workplace incivility behavior is organizational climate. This study aims to determine the relationship between organizational climate and workplace incivility behavior in nurses in Makassar City. This study used a quantitative correlation approach. Respondents in this study were 134 nurses in Makassar City who were obtained using accidental sampling. The results indicate that there is a negative and significant relationship between organizational climate and workplace incivility behavior in nurses in Makassar City (r = -0.318; p = 0.000) where the higher the organizational climate score, the lower the workplace incivility behavior score, and vice versa. The implication in this study can be a foundation for hospitals to minimize workplace incivility behavior by forming a positive organizational climate.